Male college students' accounts of their resilience from risky behaviors during adolescence: a qualitative analysis - Hiveley, Matthew Thomas (2010)
Using grounded theory with a constructivist perspective, this study sought to gain greater insight and understanding regarding how a select group of males were able to demonstrate resilience by overcoming risky behaviors. Male college students with past engagement in risky behaviors were interviewed to gain their perceptions of what helped them to discontinue their risky behaviors during adolescence and demonstrate resilience. Participants were asked to share what it was that specifically contributed to their risky behaviors and themes were developed based on their responses using a grounded theory method to further understand what helped them to demonstrate their resilience. Implications are discussed regarding how these results can help current adolescents who are struggling with engagement in risky behaviors and how adults surrounding these adolescents can provide the needed support and assistance with these behaviors, as well as ideas for future research